Coconut shell waste-derived graphene oxide composite with neodymium oxide (Nd2O3) for advanced applications - E.H. Sujiono; A.M.A. Saputra; Muchlis; B.D. Usman; Nur Fadilah; Zurnansyah; D. Zabrian; N. Azizah; Samnur (Results in Materials, 2023)
This paper reports the synthesis and physical properties of graphene oxide/neodymium oxide (GO/Nd2O3) composites. The GO/Nd2O3 composite was prepared by a simple Sonochemical Method, and graphene oxide was synthesized by a modified hummers method. The synthesized composites were characterized by using X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FT-IR), Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), Raman Spectroscopy, and UV–Vis Spectroscopy. The XRD data confirmed that the GO/Nd2O3 composite had a hexagonal phase structure and showed that the more Nd2O3 nanoparticles were added to GO, the more the crystallinity index increased. The FT-IR spectra showed six types of bonds of functional groups of the GO/Nd2O3 composite, namely the hydroxyl (-OH), carbonyl (C]O), (C]C), (C–O–H), (C–O–C), and the absorption band at 678 cm−1 shows REOs (Nd2O3). Raman spectroscopic analysis showed that the intensity of the ratio of ID/IG was (∼0.85) with the size of sp2 graphitic area of ∼22.6 nm. The addition of Nd2O3 particles to GO did not affect the intensity ratio of ID/IG and was almost the same for the GO and GO/Nd2O3 composite. SEM results show that the composite has a porous three-dimensional carbon network structure. The optical properties were analyzed using UV–Visible spectroscopy. The results of Urbach Energy showed that the GO/Nd2O3 composite is a semiconductor material with an Urbach Energy value of 0.050–0.063 eV, showing the potential application of GO/Nd2O3 composites in electronic devices.